2018
DOI: 10.1371/journal.pntd.0006332
|View full text |Cite
|
Sign up to set email alerts
|

Association between gastrointestinal tract infections and glycated hemoglobin in school children of poor neighborhoods in Port Elizabeth, South Africa

Abstract: BackgroundLow- and middle-income countries are facing a dual disease burden with infectious diseases (e.g., gastrointestinal tract infections) and non-communicable diseases (e.g., diabetes) being common. For instance, chronic parasite infections lead to altered immune regulatory networks, anemia, malnutrition, and diarrhea with an associated shift in the gut microbiome. These can all be pathways of potential relevance for insulin resistance and diabetes. The aim of this study was to investigate the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Both urogenital schistosomiasis and IPIs have been linked to increased morbidity and mortality and serious complications. Intestinal parasitosis impairs the body's metabolism, nutrition absorption, and gut ecosystem [24][25][26]. A complicated relationship exists between parasitosis and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Both urogenital schistosomiasis and IPIs have been linked to increased morbidity and mortality and serious complications. Intestinal parasitosis impairs the body's metabolism, nutrition absorption, and gut ecosystem [24][25][26]. A complicated relationship exists between parasitosis and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in other studies of patients with T2DM, a positive association between H. pylori infection and suboptimal glycemic control was shown (19,20). A positive association was previously noted between H. pylori infection and prediabetes (11,12). Draz et al (11) assessed the association between HP and prediabetes in adults using the oral glucose tolerance test (OGTT) for prediabetes diagnosis and histopathological examination for H. pylori diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (10) found that gastric H. pylori infection is associated with the risk of diabetes mellitus but not prediabetes. Recent studies have shown a positive association between H. pylori infection and prediabetes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…An infection with S. stercoralis was found positively associated with severe DM [ 36 ]. We reported a positive association of H. pylori infections with HbA1c in school children from poor neighbourhoods in South Africa, but neither a cross-sectional association with other common helminth infections nor a change in HbA1c as a result of anti-helminthic treatment [ 37 ]. It has been shown that socioeconomic, environmental and behavioural factors influence the prevalence and intensity of helminth infections and could therefore, in part, be confounders as well as mediators of any association with diabetes [ 18 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we used an internationally certified HbA1c test, which was able to capture most of the previously diagnosed DM cases. The HbA1c point-of-care method applied was validated for use in hot and remote low-income settings in the context of our previous study in South Africa [ 37 ]. The validity of our HbA1c findings is further supported by their positive association with validated DM risk factors such as age, BMI and smoking.…”
Section: Discussionmentioning
confidence: 99%